Overall Structural Model of NS5A Protein from Hepatitis C Virus and Modulation by Mutations Confering Resistance of Virus Replication to Cyclosporin A - Badillo, Aurélie; Bartenschlager, Ralf; Lohmann, Volker (Biochemistry, 2017)
Hepatitis C virus (HCV) nonstructural protein 5A (NS5A) is a RNA-binding phosphoprotein composed of a N-terminal membrane anchor (AH), a structured domain 1 (D1), and two intrinsically disordered domains (D2 and D3). The knowledge of the functional architecture of this multifunctional protein remains limited. We report here that NS5A-D1D2D3 produced in a wheat germ cell-free system is obtained under a highly phosphorylated state. Its NMR analysis revealed that these phosphorylations do not change the disordered nature of D2 and D3 domains but increase the number of conformers due to partial phosphorylations. By combining NMR and small angle X-ray scattering, we performed a comparative structural characterization of unphosphorylated recombinant D2 domains of JFH1 (genotype 2a) and the Con1 (genotype 1b) strains produced in Escherichia coli. These analyses highlighted a higher intrinsic folding of the latter, revealing the variability of intrinsic conformations in HCV genotypes. We also investigated the effect of D2 mutations conferring resistance of HCV replication to cyclophilin A (CypA) inhibitors on the structure of the recombinant D2 Con1 mutants and their binding to CypA. Although resistance mutations D320E and R318W could induce some local and/or global folding perturbation, which could thus affect the kinetics of conformer interconversions, they do not significantly affect the kinetics of CypA/D2 interaction measured by surface plasmon resonance (SPR). The combination of all our data led us to build a model of the overall structure of NS5A, which provides a useful template for further investigations of the structural and functional features of this enigmatic protein.